2021
DOI: 10.1016/j.jenvman.2021.112166
|View full text |Cite
|
Sign up to set email alerts
|

Public transit usage and air quality index during the COVID-19 lockdown

Abstract: The people suffering from coronavirus have to lead unprecedented actions including limiting travel especially using public transportation. Therefore, lockdown measures and social distancing to decelerate the distribution of the COVID-19 has become the new norm. Nevertheless, improvement in the ambient air quality of the cities globally has appeared as a key advantage of this lockdown. There is a lack of research in the field of public transportation mobility and the Air Quality Index (AQI) during the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 46 publications
2
48
1
2
Order By: Relevance
“…While studies hypothesize reductions in industrial production, transportation and other human activities are responsible for the lower levels of ambient air pollution that occurred during COVID-19 lockdowns, they typically do not make a direct link to specific activities. Exceptions include Sahraei et al (2021) which shows that in 12 countries with lockdowns there was a concurrent decrease in public transit usage, and Dang and Trong (2020) , which used Google Mobility Reports to show lower mobility in locations where government policies were more stringent. Likewise, Zeng and Bao (2021) finds that much of the decrease in PM 10 , PM 2.5 and NO 2 that occurred during lockdowns was due to lower levels of human migration.…”
Section: Introductionmentioning
confidence: 99%
“…While studies hypothesize reductions in industrial production, transportation and other human activities are responsible for the lower levels of ambient air pollution that occurred during COVID-19 lockdowns, they typically do not make a direct link to specific activities. Exceptions include Sahraei et al (2021) which shows that in 12 countries with lockdowns there was a concurrent decrease in public transit usage, and Dang and Trong (2020) , which used Google Mobility Reports to show lower mobility in locations where government policies were more stringent. Likewise, Zeng and Bao (2021) finds that much of the decrease in PM 10 , PM 2.5 and NO 2 that occurred during lockdowns was due to lower levels of human migration.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, o transporte público nas capitais é oferecido principalmente por linhas de ônibus e sistemas ferroviários (metrô) (SAHRAEI; KUŞKAPAN;ÇODUR, 2021). O país já experimentava grandes aglomerações no transporte público antes da pandemia e a incapacidade de suprir a demanda de modo equilibrado.…”
Section: Resultsunclassified
“…Studies have shown that public transport ridership has not been shown to increase COVID-19 cases with proper precautionary measures such as social distancing, increased air circulation, mandatory face coverings [92]. However, the uneasiness of shared public spaces during the COVID-19 lockdown resulted in up to an 80-90% decrease in public transport ridership, globally, leading to significant improvements to air quality due to the reduction of public transportation operation [88,93]. The aversion to public transport during COVID-19 has resulted in the increased uptake and encouragement of outdoor, private modes of transport such as bicycling and walking [94].…”
Section: Discussionmentioning
confidence: 99%
“…Access to an affordable, personal means of transportation has implications beyond mobility, but also for safety. This has been highlighted during the COVID-19 pandemic, during which public transport ridership dramatically decreased due to the unease of traveling with strangers [88]. There is opportunity for further research on overcoming the challenges of integrating ECS to adapt to user behavior and lifestyles and on the potential for ECS to offer an equitable alternative to the high upfront cost of electric vehicle ownership.…”
Section: Shared Electric Mobilitymentioning
confidence: 99%